Relationship between electromagnetic characteristics of transitions and different interconnect angles in microwave communication circuits - Jin-shan GU; Gui WANG; Bin-feng YAN (Tongxin xuebao)
Transmission lines connected to the two ends of via in coplanar waveguide (CPW) to CPW transition and/or CPW to microstrip (MS) transition are not always in line,but in arbitrary angle.The propagation characteristics of these structures are simulated and analyzed.The simulation results indicate that scatter parameters of the transition structures are affected by the angle of two transmission lines.In general,as angle increases,|S11| of both transitions increases,while|S21| decreases.The change tendency of S-parameters is different when angle is more than or less than 90°,especially when angle is 180°.In addition,propagation characteristics of CPW-CPW and CPW-MS transitions are different,and the explanation is given.